Chemical composition of ferromanganese nodules and crust from the Northwest Pacific Ocean - T Uchio (PANGAEA, 2023)
Manganese nodules and crust were retrieved during the KH-68-3 campaign of the R/V Hakuho-Maru. Their chemical composition was determined by a combination of methods: traditional wet chemistry, atomic absorption spectroscopy and gravimetric analysis.